1992
DOI: 10.1152/ajpheart.1992.262.1.h117
|View full text |Cite
|
Sign up to set email alerts
|

Halothane anesthesia abolishes pulmonary vascular responses to neural antagonists

Abstract: We investigated the effects of the inhalational anesthetic halothane on autonomic nervous system (ANS) regulation of the baseline pulmonary vascular pressure-flow (P/Q) relationship compared with that measured in the conscious state. Multipoint pulmonary vascular P/Q plots were constructed by stepwise constriction of the thoracic inferior vena cava to decrease venous return and Q. P/Q plots were generated in the same dogs in the conscious state and during halothane anesthesia (approximately 1.2% end tidal) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This may simply indicate that in the absence of an exercise‐generated, sensitizing level of metabolites in the muscle interstitium, activation of the mechanoreflex by the standardized stretch was less effective than in the exercise trial (Drew et al 2008, 2009). However, the effects of atropine on the pulmonary vasculature are known to depend on cardiac output and hence pulmonary blood flow (Murray et al 1986; Chen et al 1992). In conscious dogs, Chen and co‐workers (1992) observed that the pulmonary pressure to flow ratio was not affected by atropine during conditions of low cardiac output but it was reduced during higher cardiac output conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may simply indicate that in the absence of an exercise‐generated, sensitizing level of metabolites in the muscle interstitium, activation of the mechanoreflex by the standardized stretch was less effective than in the exercise trial (Drew et al 2008, 2009). However, the effects of atropine on the pulmonary vasculature are known to depend on cardiac output and hence pulmonary blood flow (Murray et al 1986; Chen et al 1992). In conscious dogs, Chen and co‐workers (1992) observed that the pulmonary pressure to flow ratio was not affected by atropine during conditions of low cardiac output but it was reduced during higher cardiac output conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of atropine on the pulmonary vasculature are known to depend on cardiac output and hence pulmonary blood flow (Murray et al 1986; Chen et al 1992). In conscious dogs, Chen and co‐workers (1992) observed that the pulmonary pressure to flow ratio was not affected by atropine during conditions of low cardiac output but it was reduced during higher cardiac output conditions. In the limited literature based on human studies, administration of atropine induces increased cardiac output accompanied by mildly decreased pulmonary artery pressures (Daly et al 1963).…”
Section: Discussionmentioning
confidence: 99%
“…Our experimental approach has several unique features that allow our results to be attributed specifically to the effects of CPB. First, general anesthetics are recognized as modulators of vasoregulation, including pulmonary vasoregulation (5,12,22,23,25). The use of conscious animals avoids this potential confounding influence.…”
Section: Discussionmentioning
confidence: 99%
“…The LP-Q relationship was measured to determine the pulmonary vascular responses to endothelium-dependent and -independent vasodilators before and again 3-4 days after closed-chest CPB. This approach avoids the known effects of general anesthesia on neurohumoral (5,12,23,25) and local (12,19,22) mechanisms of pulmonary vasoregulation. Furthermore, measurement of continuous LP-Q plots avoids the inherent limitations of single-point calculations of pulmonary vascular resistance.…”
mentioning
confidence: 99%